2017
DOI: 10.1007/s12041-017-0810-y
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation of HOXA13 underlies hand-foot-genital syndrome in a Chinese family

Abstract: Hand-foot-genital syndrome (HFGS) is a rare autosomal dominant inherited syndrome characterized by limb malformations and urogenital defects. HFGS is caused by mutations in the HOXA13 gene. The aim of this study was to identify causative mutations in individuals and to explore the molecular pathogenesis in a Chinese family with HFGS. We performed Sanger sequencing and identified a recurrent missense mutation in the homeodomain (c.1123G>T, p.V375F) of HOXA13, molecular modelling predicted the mutation would aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…HOXA13 encodes a DNA-binding transcription factor and may regulate gene expression, morphogenesis, and differentiation. It has been reported that mutated HOXA13 associated with the limb and genitourinary deformity development and can cause handfoot-genital syndrome [27]. Additionally, HOXD10 is expressed in the development of limb buds and is involved in differentiation and limb development.…”
Section: Discussionmentioning
confidence: 99%
“…HOXA13 encodes a DNA-binding transcription factor and may regulate gene expression, morphogenesis, and differentiation. It has been reported that mutated HOXA13 associated with the limb and genitourinary deformity development and can cause handfoot-genital syndrome [27]. Additionally, HOXD10 is expressed in the development of limb buds and is involved in differentiation and limb development.…”
Section: Discussionmentioning
confidence: 99%
“…And our previous research identified a novel mutation of HOXA10 in a patient with didelphic uterus [ 29 ]. Moreover, several nonsense mutations (p.W369X, p.S136X, p.Q196X, and p.Q365X), missense mutations within the homeodomain (p.I368F, p.N372H and p.V375F), and in-frame polyalanine expansions of HOXA13 gene have been found to cause Müllerian duct fusion defects in patients with hand-foot-genital syndrome [ 14 , 30 32 ]. Taken together, these results suggest that HOX genes might play important roles in the fusion of the Müllerian duct and in the resorption of the uterine septum.…”
Section: Discussionmentioning
confidence: 99%
“…That indicates the role of genetic factors in the pathogenesis of MDAs, but the pathogenic genes are still unclear. Previous studies have found that mutations or copy number variations (CNVs) in the genes, including TBX6 , HNF1B , HOXA13 , HOXA10 , LHX1 , PBX1 , WNT9B , EMX2 , CRKL and TP63 , are associated with MDAs.…”
Section: Introductionmentioning
confidence: 99%